Women’s Representation in the Indonesian Parliament and the Impact of the 30 Percent Quota on Gender-Responsive Policies - Amylia Nurul Fitri N (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
This study examines women’s representation in the Indonesian legislature and the factors influencing the achievement of the 30% minimum quota. Using a normative legal research method with statutory and conceptual approaches, the study analyzes relevant regulations and internal party mechanisms. The findings reveal that although women’s representation has increased nationally, it remains below the quota target, with notable variations across provinces. Major challenges include structural, technical, and socio-cultural factors such as patriarchal culture, limited access to resources, non-strategic candidate placement, and gender-based political violence. Based on Pitkin’s theory of representation, the analysis shows that the growing number of female legislators tends to strengthen descriptive representation but does not yet significantly enhance substantive policy influence. The discussion compares these findings with previous studies and highlights the need for a dual strategy: internal party reform and cultural intervention to strengthen women’s substantive participation. In conclusion, improving women’s representation requires synergy between regulations, implementation mechanisms, and political culture transformation to produce gender-responsive public policies.